EVALUASI ANALISIS RISIKO KEUANGAN UNTUK PENINGKATAN BISNIS - Basory, Hartomy Akbar; Ditasila, Annisa; Pratama , Bagas Brian; Isadora; Pavlova, Khristina Alexandrovna (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The company is Focus Technology LLC, main focus is ‘Made-in-China.com’, as this object research, which was founded in 1996. The research method and analysis used in this research are the Mixed Method, which is a research method that integrates quantitative and qualitative methods. The data sources in this research consist of: 1) Primary data, namely data obtained from the field or data sourced from informants; 2) Secondary data is data obtained through books, notes, documents, or literature in other readings that are used as theory. The result of research is discoveries that provide answers to problems, namely the integral score of the financial condition of the economic management system method. This research aims to present and analyse related financial risk management in digital companies. The integration of technology companies, such as digital business and e-commerce, will bring initial changes to the way a technology company identifies, measures, and manages financial risks. Conclusions about this research are presented, and recommendations to improve the activities of the organisation are considered. Current liabilities remained unchanged at around RMB 1 billion or approximately $ 137 million in both years. This indicates the stability of the company's financial position and its ability to manage its liabilities.